(untitled) (The Research of Medical Science Review, 2024)
OBJECTIVE: To determine the efficacy of lactulose versus refixamine plus lactulose for prophylaxis of portosystemic encephalopathy.METHODOLOGY: A randomized controlled trial was conducted in the Department of Gastroenterology at the Asian Institute of Medical Sciences (AMIS) Hospital, Hyderabad. Non-probability purposive sampling technique was used to recruit the sample of 166 patients between aged group of 20 to 70 years, of either gender. Participants had to have a confirmed diagnosis of portosystemic encephalopathy (PSE) were included in the study. Participants were randomized into two equal groups (n=83) by using computer-generated sequential numbers enclosed in sealed envelopes, which were opened at the time of allocation. Group A received a combination therapy of lactulose and rifaximin (400 mg twice daily), while Group B received lactulose alone (30–60 mL daily in 2–3 divided doses). Participants were followed for one week to assess treatment efficacy of the treatment. SPSS version 26.0 was used to analyse the data. The P value ≤ 0.05 was considered as criteria of statistical significance. RESULTS: The mean age of participants in Group A was 46.63 ± 11.75 years, while in Group B, it was 44.19 ± 11.53 years, with insignificant difference between the groups (p = 0.180). In gender distribution group A consist of 66.3% males and 33.7% females while group B included 59.0% males and 41.0% female. Ammonia levels were significantly higher in Group A (131.45 ± 22.42 µmol/L) compared to Group B (119.58 ± 21.72 µmol/L, p = 0.001). Efficacy in Group A versus Group B was noted as (71.1% v/s 53.0%; OR: 2.18; p=0.016).CONCLUSION: The findings of current study shows that combination of lactulose and rifaximin found to be significantly more effective than lactulose alone in the treatment of portosystemic encephalopathy. Patients receiving combination therapy had rates of clinical outcomes, and better biochemical profiles. These findings support lactulose plus rifaximin as a superior treatment option for PSE.